1999
DOI: 10.1007/s11886-999-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

Beta-blockers and amiodarone for the primary prevention of sudden cardiac death

Abstract: Sudden cardiac death remains a major public health care problem, generally occurring in patients with ventricular dysfunction. Beta-blockers, already of proven benefit for patients after myocardial infarction, have recently been shown to improve functional status and mortality outcomes in patients with heart failure. Amiodarone, a potent antiarrhythmic drug, was recently studied in a number of randomized clinical trials involving patients with heart failure and patients after myocardial infarction. Routine use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…However, in a post‐hoc analysis it was found that lower serum digoxin concentrations are associated with improved survival [31]. A clinically relevant reduction of the risk of sudden cardiac death could be demonstrated for β‐blocking agents alone [32 34].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a post‐hoc analysis it was found that lower serum digoxin concentrations are associated with improved survival [31]. A clinically relevant reduction of the risk of sudden cardiac death could be demonstrated for β‐blocking agents alone [32 34].…”
Section: Discussionmentioning
confidence: 99%
“…37,41,63 As the neurohormonal hypothesis emerged, so too did a new understanding of the potential role of ␤-blockers in heart failure. Although acute treatment with ␤-blockers decreases blood pressure and cardiac index, long-term administration of ␤-blockers is associated with significant increases in ejection fraction [64][65][66][67][68][69][70][71][72][73][74][75][76][77] and cardiac index and a decrease in left ventricular (LV) end diastolic pressure. 61,[77][78][79][80][81][82][83][84][85][86][87] ␤-Blockers reverse the deleterious changes associated with LV remodeling and decrease myocardial mass and LV volume, leading to improved hemodynamics.…”
Section: Laboratory Sciencementioning
confidence: 99%